PENGARUH PROMOSI PADA PENINGKATAN PENJUALAN PADA CV. AGRA UTAMA PALEMBANG - EFRINA MASDAINI (Jurnal Manajemen Bisnis Unbara, 2022)
Abstract The study entitled The Effect of Promotion on Increasing Sales at CV. AGRA UTAMA Palembang discusses how promotions are carried out on CV. AGRA UTAMA Palembang does it have a significant influence on increasing sales. The data used are primary data and secondary data which are then analyzed qualitatively by describing the existing problems to then be analyzed based on Marketing Management theories. Based on the results of the study, it was concluded that in the Validity Test it can be seen that the value of r calculated for all indicators tested is positive and greater than the r table value which is 0.44, in Simple Linear Regression where the Summary Model Table displays the value of R which is symbol of the value of the correlation coefficient. In this study the correlation value was 0.028. In the ANOVA table above, sig 0.939 is obtained, which means <significant criterion (0.05). Thus the regression equation model based on research data is significant, meaning that the linear regression model is influenced/has linearity criteria.